If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -3x = 16 + 12x Solving 6 + -3x = 16 + 12x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12x' to each side of the equation. 6 + -3x + -12x = 16 + 12x + -12x Combine like terms: -3x + -12x = -15x 6 + -15x = 16 + 12x + -12x Combine like terms: 12x + -12x = 0 6 + -15x = 16 + 0 6 + -15x = 16 Add '-6' to each side of the equation. 6 + -6 + -15x = 16 + -6 Combine like terms: 6 + -6 = 0 0 + -15x = 16 + -6 -15x = 16 + -6 Combine like terms: 16 + -6 = 10 -15x = 10 Divide each side by '-15'. x = -0.6666666667 Simplifying x = -0.6666666667
| 3a-15=6 | | -7x+14=21 | | -20-6m=4m | | 3(6x+2)=2x+10 | | 15x+-1=-16 | | 10(x+12)+50x+20(2x+4)=1400 | | -4.1=-12.3k | | x=log(1.035) | | 3x+8=1 | | x^2+5x-26=5x-10 | | -10b=24+b | | 21-3s=s+5 | | fart=traf | | 3w^2+20w+144=2w^2-4w | | log(1.035)=x | | 8x-7=3x-74 | | -x+-7=18 | | 6x-x^2=-40 | | 4+10s-4s= | | 4s^2-4s+52=3s^2+13s | | -14x+-20=8 | | x-0.8=9.1 | | x-7+2x+4=101 | | log(1.035)=log(1) | | (3x+2)(4x+1)= | | x^2+2x+99999999999999999x=0 | | 2x^2+5x-3=4 | | 0.10x+0.25(x+10)+0.05(4)(x+10)=6.15 | | 2a^2*5a= | | 6x^2+24x-8=0 | | e^2=16e-48 | | 9(2x+4)=0 |